Household Debt, Consumption, and Monetary Policy in Australia - Loukoianova, Elena (IMF Working Papers; Working Paper, 2019)
This paper discusses the evolution of the household debt in Australia and finds that while higher-income and higher-wealth households tend to have higher debt, lower-income households may become more vulnerable to rising debt service over time. Then, the paper analyzes the impact of a monetary policy shock on households' current consumption and durable expenditures depending on the level of household debt. The results corroborate other work that households' response to monetary policy shocks depends on their debt and income levels. In particular, households with higher debt tend to reduce their current consumption and durable expenditures more than other households in response to a contractionary monetary policy shocks. However, households with low debt may not respond to monetary policy shocks, as they hold more interest-earning assets.